The Quantum Electro Dynamics Formulization; the Atom; its Architecture and Related Quantum Phenomenons - Ahmed, Sabbir (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Quanta in a quantum means a point in a smallest Possible space. the other related pieces are that where is this space and how is it defined. wether it is possible to get values out of calculations out of dividing 0 or a point. rooting twice and triple time in following calculations means its quantizing down to its root. and yet keeping the construct of logic that is semi Pythagorean. the base of it all is a tetrahedron and at the end of it all what is defined is a tetrahedron. its a calculation rather than a theory. the theory emerges from the calculation. nobody ever deigned energy. there are types of calculations to measure energy. but like force it is a phenomenon. but to calculate the base of quanta we need a base. and the base is energy. is it is important define what energy is. other wise there is no possibility of calculating what quanta or quantum is. this defines all the particles found by CERN. the Source of the values are converted into this theories base measurement scale index. or MEV. the GEV converses is avoided and used as a square of MEV. but except for Higgs which is not understood and self theorized like everything else. It is unto you to accept the definition and validity since the values are quite closely matched. it is not the intention of writing this paper to explain an experimenting and how it matches the mathematics. It is mathematics. But written in english. it is written in C#.  Again for easier comprehension. as greek letters are often confused by the power of the Gods. As in Hydra or something. That has been taken care of. A point to note are the catalyst agents used from the form of energy conversions. To Force charge and Mass. you would find that the whole theory started off from nothing or everything empty and in a shell of existence that I have defined to be energy. And everything else that has been calculated are geometric or pythagorean. Not in the sense of triangles but to the point of architecture.That everything that is floating must have a propagation path and it converges and diverges to inwards and outwards. A more clarified intention of mathematics will be comprehended upon looking at the equations. A problem to be faced was the scale match with the cern mega electron volt and the classical kgs and newtons. However that has been solved by quantizing the speed of light and using the mass number and energy to be the mega electron volt. As you would see that it makes sense that if a light is moving at a speed of km to 100000 it is also possible to have the same speed if its moving .1000000 in x_plank scale or ppx.